Desain proses pengeringan semprot untuk produksi tepung karet alam dari lateks - Abidin, A. Zainal; Vachlepi, Afrizal (Jurnal Teknik Kimia Indonesia, 2012)
Spray drying process design for the production of natural rubber powder from latexHigh water content in latex may result in perishable condition, high transportation costs, large packing needs, and handling difficulty due to the use of ammonia to prevent its coagulation.  A solution to this problem is to convert the latex into rubber powder using spray drying.  This work describes the design of the rubber powder production process, feedstock formulation, and the design of the dryer. Spray dryer performance is evaluated by simulation. The production process involves latex collection, quality inspection, filtration, addition of additives, and spray drying. Feedstock formulation consists of fresh latex, 1 %-w anticoagulant, and 2 %-w non-stick agent. The drying chamber is designed with a latex feed rate of 6x10-5 m3/s, moisture content of 80 %-w, density of 920 kg/m3, feed temperature of 27 oC, and drying air temperature of 140 oC. A pressurized-type nozzle is selected for the dryer. Design calculation results indicate that the dryer requires a nozzle diameter of 3.5 mm, chamber volume of 0.8 m3, cylindrical section height of 850 mm, conical section height of 870 mm, and a chamber diameter of 1000 mm. Drying time is 0.134 sec, with an overall residence time of 1.80 second. The dryer is predicted to produce natural rubber powder with a moisture content of 0.32-0.56 %-w.Keywords: latex, design, spray drying, simulation AbstrakKandungan air yang tinggi di dalam lateks dapat mengakibatkan lateks mudah rusak, biaya transportasinya tinggi, kebutuhan kemasannya besar, dan penanganannya yang ketat karena lateks mengandung amonia sebagai bahan pencegah kerusakan. Salah satu cara mengatasinya adalah mengkonversi lateks tersebut menjadi tepung karet alam dengan teknologi pengeringan semprot (spray drying). Di sini akan dipaparkan perancangan proses produksi tepung tersebut, formulasi umpannya, dan pengering semprot (spray dryer) yang digunakan untuk mengeringkan lateks. Kinerja dari pengering semprot dievaluasi dengan teknik simulasi. Rancangan proses produksi dimulai dari pengumpulan lateks, pemeriksaan kualitas lateks, penyaringan, penambahan zat aditif, dan pengeringan semprot. Formulasi umpan terdiri dari lateks segar, antikoagulan 1%-b, dan antilengket 2 %-b. Ruang   pengering semprot dirancang berdasarkan laju alir umpan lateks 6x10-5 m3/s dengan kadar air 80 %-b, densitas 920 kg/m3, suhu umpan 27 °C, dan udara pengering 140 °C. Nozzle bertekanan dipilih untuk alat ini. Hasil desain menunjukkan bahwa pengering semprot memerlukan diameter lubang nozzle 3,5 mm,volume ruang pengering 0,8 m3, tinggi bagian silinder 850 mm, kerucut 870 mm, dan diameter 1000 mm. Waktu pengeringan umpan berlangsung selama 0,134 detik dengan waktu lintasan 1,80 detik. Hasil simulasi menunjukkan pengering semprot mampu menghasilkan tepung karet alam dengan kadar air sekitar 0,32-0,56%.Kata kunci: lateks, perancangan, pengeringan semprot, simulasi